School Fees : A Roadblock to Education For All - Bentaouet Kattan, Raja; Burnett, Nicholas (World Bank, Washington, DC, 2012)
There is increasing momentum on the road to Education for All (EFA), but school fees are still a roadblock for too many children. Several African countries have recently abolished school fees outright. The dramatic surge in enrollments that followed, is strong evidence that the payment of fees can be a major obstacle to enrollment. The note examines the prevalence of fees, and their impact worldwide, and draws lessons involved in attempts to eliminate user fees, and to provide alternate sources of financing. Some important lessons are being learned from these efforts, namely, that fees cannot be abolished without consideration of whether, and how, they should be replaced by an alternative source of income. Replacement revenues can be provided by simply increasing expenditures on education, by improving the efficiency of education spending, or by use of debt relief funds to close the financing gap.